Epitranscriptomic Analysis of m6A Methylome After Peripheral Nerve Injury - Zhang, Lei; Hao, Dingyu; Ma, Pengyi; Ma, Boyuan; Qin, Jia; Tian, Guangyuan; Liu, Zihao; Zhou, Xianhu (Frontiers in Genetics, 2021)
N6-methyladenosine (m6A) is one of the most plentiful internal RNA modifications, especially in eukaryotic messenger RNA (mRNA), which plays pivotal roles in the regulation of mRNA life cycle and nerve development. However, the mRNA m6A methylation pattern in peripheral nervous injury (PNI) has not been investigated. In this study, sciatic nerve samples were collected from 7 days after sciatic nerve injury (SNI) and control rats. Quantitative real-time PCR demonstrated that m6A-related methyltransferase/demethylase genes were remarkably upregulated in SNI group compared with control group. Methylated RNA immunoprecipitation sequencing (MeRIP-seq) was performed to reveal the m6A methylation landscape. The results showed that 4,014 m6A peaks were significantly altered, including 2,144 upregulated and 1,870 downregulated m6A peaks, which were corresponded to 1,858 genes. Moreover, 919 differentially expressed genes were identified by the conjoint analysis of MeRIP-seq and RNA-seq. GO and KEGG pathway analyses were performed to determine the biological functions and signaling pathways of the m6A-modified genes. Notably, these genes were mainly related to the immune system process, cell activation, and nervous system development in GO analysis. KEGG pathway analysis revealed that these genes were involved in the cell cycle, B cell receptor signaling pathway, axon guidance pathway, and calcium signaling pathway. Furthermore, the m6A methylation and protein expression levels of autophagy-related gene (Atg7) were increased, together with the activation of autophagy. These findings shed some light on the epigenetic regulation of gene expression, which may provide a new opinion to promote functional recovery after PNI.